Identifikasi Pola Struktur Geologi Sebagai Pengontrol Sebaran Mineral Radioaktif Berdasarkan Kelurusan Pada Citra Landsat-8 di Mamuju, Sulawesi Barat - Indrastomo, Frederikus Dian; Sukadana, I Gde; Suharji (BRIN Publishing, 2017)
Mamuju area and its surrounding are composed of volcanic rock containing uranium (U) and thorium (Th) elements. Radioelements concentrations in the area reach 1,529 ppm eU and 817 ppm eTh. Radioactive minerals identified in the area are thorianite, davidite, gummite, and autunite. The geological structures were formed by tectonic activities which controlled the creation of volcanic complex and U-Th mineralization in the complex. Identification of geological structure in the field is very difficult due to densely vegetation and higly degree of weathering. The interpreted lineaments from Landsat-8 imagery are the manifestation of geological structures which have controlled the existence of U and Th. Lineaments analysis using Sastratenaya formula is used to obtain the relative age and chronologies of the lineaments. Dose rate measurements in the area show the trend of radioactivitiy anomalies are trending northwest–southeast. The Sastratenaya formula results the formed structures are relatively older and dominantly directing northwest–southeast (N 140o–150o E). Based on the linement interpretation, the dominant direction has similliarity with volcanic and radioactivity distribution. Structures which controlling the volcanic formation and related to U and Th mineralization generally are the northwest–southeast trending structures, which were created along with U and Th mineralization.